The Effect of Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) And Net Profit Margin (NPM) on Financial Performance of Bank DKI - Sri Retnaning Sampurnaningsih; Cahya Irani; Sahroni Sahroni; Zulfitra Zulfitra; Denok Sunarsi (Program Pascasarjana Universitas Negeri Makassar, 2021)
The purpose of this study was to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Net Profit Margin (NPM) on Financial Performance at PT Bank DKI, period 2010 - 2019. The method used is descriptive quantitative by using classical assumption test, Multiple Linear Regression, T-test, F-test, and Coefficient of Determination Test. The t-test results showed that CAR has no significant effect on ROA. LDR has no significant effect on ROA. NPM has a significant positive effect on ROA. The F-test results showed that simultaneously CAR, LDR, NPM have a significant effect on ROA at PT Bank DKI for the 2010-2019 period. The coefficient of determination test results showed the contribution of the independent variables Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Net Profit Margin (NPM) to Return On Assets (ROA), (by Adjusted R2) is 72.5% and the remaining 27.5% is influenced by other factors. The limitation of this research is the sampling of research using the financial statements of 2010 – 2019. The variables taken are only limited to banking fundamental factors, namely liquidity ratios and profitability ratios. This research is expected to enrich information as a reference as well as literature on banking financial performance by using banking fundamental ratios, namely Capital Adequacy Ratio (CAR), Loan to Deposits (LDR), Net Profit Margin (NPM) and Return On Assets (ROA).